Az autóbusszal közlekedő utasokat az Európai Unióban megillető jogok - Zoványi, Nikolett (Debreceni Jogi Műhely, 2013)
The European Parliament and the Council adopted new rules for passengers traveling by buses. The 181/2011/EU Regulation concerning the rights of passengers in bus and coach transport developed a strict liability of bus carriers in cases of delay and cancellation. It deals with accidents, the meaning of right to information, handling of complaints, and the non-discrimination and mandatory assistance for disabled persons and persons with reduced mobility.The Regulation is entered into force on March 21st 2013. The article is about to analyze the content and the meaning of these new rules and rights passengers have when they use bus transportation.